EMPOWERMENT IN ACCELERATING THE GROWTH OF STUNTED TODDLERS' HEIGHT BY IMPROVING BIOACUPRESSURE MASSAGE SKILLS FOR HEALTH CADRES AT THE BANJAR I SUB-DISTRICT HEALTH CENTER IN BULELENG DISTRICT - Ribek, Nyoman; Surasta, I Wayan; Labir, I Ketut (Jurnal Pengabmas Masyarakat Sehat, 2023)
The background for conducting bioacupressure training for health cadres is to accelerate the reduction of stunting rates in the Banjar 1 Buleleng health center area. Stunting is a condition of growth failure in children due to malnutrition and lack of quality, so that body length or height has a z-score value of less than -2SD. Stunted toddlers have a negative impact on health and functional bodies and increase child morbidity. The prevalence of stunting in Buleleng is still 20.5 percent and is above the WHO setting of 20 percent. Various efforts have been made, one of which is in the Banjar sub-district, a stunting consultation group has been formed and the implementation of programs for providing supplementary food, providing vitamins and cross-sectoral improvements to sanitation . Even so, in the Banjar 1 health center area, there are still 69 stunted toddlers. The purpose of this community service is to increase the knowledge of the cadres about bioacupressure massage for stunting toddlers. The training was conducted for 40 cadres representing 11 villages in the working area of the puskesmas. The results of the training before being given training showed sufficient knowledge, there were 5 people (7.5%) who had less knowledge, 32 people (80%) had sufficient knowledge, and 12.5% (3 people) had good knowledge. After the training was carried out there was an increase in knowledge with a significant difference with the t test analysis obtained. The conclusion of the results of this community service is that the level of knowledge of health cadres about Bioacupressure massage has increased and can become a companion and motivator so that mothers who have stunted toddlers do bioacupressure massage on their toddlers so that their appetite and height growth become more maximized